Effect of germination on γ-oryzanol content of selected Sarawak rice cultivars - Kiing, Sie Cheong; Yiu, Pang Hung; Amarthalingam, Rajan; Wong, Sie Chuong (Science Publications, 2009)
Problem statement: Rice is rich in complex carbohydrates and beneficial bioactive compounds such as γ-Aminobutyric Acid (GABA), γ-oryzanol and vitamin. Several bioactive components are known to accumulate in rice during germination process. This study was to investigate the effect of germination process on γ-oryzanol levels in selected Sarawak local rice cultivars. Approach: Rice seeds were germinated for 4, 8, 12, 16, 18, 20 or 24 h at 25°C and samples were processed and analyzed for γ-oryzanol content. A partial extraction method was used for quantitative γ- oryzanol analysis. Results: Result showed γ-oryzanol concentrations in the rice cultivars varied from 0.099-0.340 mg g-1 on dry weight basis. Cultivars Udang Halus and Silah showed the highest concentration of γ-oryzanol after 16 h germination. Conclusion: The germination process exhibited diverse effects on the γ-oryzanol accumulation in rice and it was cultivar dependent.